Resistência biológica e remediação de postes de madeira tratada com CCA após 30 anos em serviço - Brocco, Lais Goncalves da Costa (2019)
The aim of this study was to evaluate the resistance to wood-destroying organisms and the efficacy of biological and chemical remediation of chromated copper arsenate (CCA) treated Corymbia citriodora poles, removed from service after 30 years. The presence of the elements arsenic (As), chrome (Cr) and copper (Cu) was quantified by inductively coupled plasma optical emission spectrometry (ICP-OES). The biological resistance of the poles was evaluated by laboratory tests with decay fungi and termites. 12 species of decay fungi were used for the biological remediation assay. For chemical remediation oxalic, citric, maleic and ethylenediamine tetraacetic (EDTA) acids were used for 24 and 48 hours. The retention between the poles and the positions tested ranged from 7.68 to 12.25 kg m-3, being generally higher in the top position and lower in the middle. The treated wood exhibited high efficiency in the biological resistance tests to decay fungi and termites in no choice feeding test, with mass losses of less than 6%. In the termite choice feeding test, mass losses ranged from 2 to 30% between the tested poles and positions (bottom, middle and top), with the highest mass losses occurring at the top (lower retention region). In biological remediation, the brown-rot fungi Wolfiporia cocos, Antrodia xantha and Fibroporia radiculosa, described as Cu tolerant, performed the best results, with the highest removals for As (59-85%) and Cr (38-61%). The Cu element was the most easily extracted, with removals above 60% among the tested fungi, being the best results (90-98%) for F. radiculosa, Coniophora puteana, Antrodia vaillantii and Postia placenta. In chemical remediation, the extraction time of 48 h was the most effective, and oxalic acid generally reached the highest removals. The EDTA + oxalic acid combination reached the highest value for Cu extraction (98%).